Assessment of Teacher -Trainees Predisposition towards the teaching Profession among undergraduates in Tertiary Institutions in Lagos State, Nigeria - Morenikeji Alex Akanmu; Comfort Olawumi Adeniyi (Indonesian Journal of Basic Education, 2023)
This study examined Teacher -Trainees Predisposition towards the teaching Profession among undergraduates in Tertiary Institutions in Lagos State, Nigeria. 390 students were purposively selected for the study but only 360 copies questionnaire which were duly filled and returned were used as the data for this study. The instrument for data collection was a researcher designed questionnaire and structured oral interview with reliability coefficient of 0.86 and 0.76 respectively. The data collected were analysed using frequency counts, mean and standard deviation. The findings from the study showed that most teacher- trainees are in the teacher education programme not because they have interest in the profession but because ,they have no other alternative. The study also discovered that Teacher-trainees’ ill perception of Teaching Profession in Nigeria is caused mainly by poor standard of living and low status accorded to teachers by the public. Hence, it was recommended among other that, the Government should boost practising teachers’ morale improving their standard of living as this will encourage the teacher- trainees and change their perception about the profession